Nesting ecology of Crocodylus acutus (Reptilia: Crocodylidae) in two locations of the coast of Oaxaca, Mexico - Cedillo Leal, César; García Grajales, Jesús; Martínez González, Juan Carlos; Briones Encinia, Florencio; Cienfuegos Rivas, Eugenia (Instituto de Ecología, A.C., 2013)
Nesting is a part of the reproductive cycle of crocodiles with the greatest impact on the survival of the species, so the objective of this study was to describe ecological aspects ofthe American crocodile (Crocodylus acutus)nesting off the coast of Oaxaca, Mexico Nine nests from two localities (La Ventanillan= 6; Palmasola n = 3) were evaluated. Field records included oviposition and hatching dates, external (distance from the center of the nest to the nearest tree and water’s edge, canopy cover) and internal (depth of the top of the nest, depth and width of the eggs chamber, humidity and pH of the top eggs chamber) nest measurements and eggs characteristics (number, fertility, length, width and weight). A Mann-Whitney test was used to compare internal and external nest variables clutches fertility and clutch size between nesting sites. A nested linear model was used to compare mean values of width, length and weight of the eggs between nesting sites. External nest variables were not significantly different (p >0.05). For inside variables, we observed only one significant difference (p =0.04), for themeanpH at the top of the nest (6.71 vs 6.01). For egg´s characteristics, means of width (4.60 vs 4.84), length (7.54 vs 7.66 cm) and weight (95.4 vs 104.4 g) of the eggs were significantly different between nesting sites. This study brings first data on nesting ecology of the American crocodile in Oaxaca and results obtained suggest a good reproductive status in the region. However, it is needed several years of data to increment the sample size and confirm the specie reproductive status.